Genetic causes of male infertility: snapshot on morphological abnormalities of the sperm flagellum - Nsota Mbango, Jean-Fabrice; Coutton, Charles; Arnoult, Christophe; Ray, Pierre F.; Touré, Aminata (Basic and clinical andrology, 2019)
Male infertility due to Multiple Morphological Abnormalities of the sperm Flagella (MMAF), is characterized by nearly total asthenozoospermia due to the presence of a mosaic of sperm flagellar anomalies, which corresponds to short, angulated, absent flagella and flagella of irregular calibre. In the last four years, 7 novel genes whose mutations account for 45% of a cohort of 78 MMAF individuals were identified: , , , , , . This successful outcome results from the efficient combination of high-throughput sequencing technologies together with robust and complementary approaches for functional validation, in vitro, and in vivo using the mouse and unicellular model organisms such as the flagellated parasite . Importantly, these genes are distinct from genes responsible for Primary Ciliary Dyskinesia (PCD), an autosomal recessive disease associated with both respiratory cilia and sperm flagellum defects, and their mutations therefore exclusively lead to male infertility. In the future, these genetic findings will definitely improve the diagnosis efficiency of male infertility and might provide genotype-phenotype correlations, which could be helpful for the prognosis of intracytoplasmic sperm injection (ICSI) performed with sperm from MMAF patients. In addition, functional study of these novel genes should improve our knowledge about the protein networks and molecular mechanisms involved in mammalian sperm flagellum structure and beating.